PERBANDINGAN PEMERIKSAAN LATERAL FLOW ASSAY CAIRAN SEREBROSPINAL DENGAN TINTA INDIA DALAM MENDETEKSI MENINGITIS KRIPTOKOKUS PADA PASIEN AIDS - Paruntu, Darell; Mawuntu, Arthur H.P; Ngantung, Danny; Bernadus, Janno B B (FAKULTAS KEDOKTERAN UNSRAT, 2017)
Background: Cryptococcal meningitis is an oppotunistic infection that may occur in AIDS patients. The definite diagnosis remains a challenge and essential in administering the standardized antifungal therapy. Lateral Flow Assay (LFA) is an easy to use antigen examination of cryptococcus that is currently being developed while Indian ink staining is a standard microscopic examination to detect the pathogen in the cerebrospinal fluid (CSF) and requires a skillful examiner. Purpose: To know whether the LFA was able to detect more cryptococcal meningitis cases than India ink staining in R.D. Kandou hospital Manado. Method: A retrospective study using CSF LFA and India ink results from hospitalized AIDS patients with intracranial opportunistic infections who undergone CSF examination. We compared the result of CSF LFA and India ink in each patients and also study the clinical characteristics of those patients. Result:We found six eligible subjects and two samples were positive for cryptococcal meningitis. All subjects were male aged of 31-40 years old. Headache was experienced by five subjects and altered consciousness. In routine CSF analysis, mean CSF protein in subjects with positive and negative results were 30 g/dl and 145 g/dl subsequently. All samples tested positive for CSF India ink also positive for CSF LFA and samples tested negative for CSF India ink also negative for CSF LFA. Conclusion: CSF LFA was not better than CSF India ink stain in detecting cryptococcal meningitis in our study. However, LFA has advantage over India ink stain in the circumstance where no skillful examiner is available.Keywords: Cryptococcal meningitis, Lateral Flow Assay, Indian Ink